2023
DOI: 10.3390/jcm12031232
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Parameters to Predict Malignant Events in Arrhythmic Mitral Valve Prolapse Population

Abstract: Bileaflet Mitral Valve Prolapse (bMVP) has been linked to major arrhythmic events and sudden cardiac death (SCD). Consistent predictors in this field are still lacking. Echocardiography is the best tool for the analysis of the prolapse and its impact on the ventricular mechanics. The aim of this study was to find new echocardiographic predictors of malignant events within an arrhythmic MVP population. We evaluated 22 patients with bMVP with a transthoracic echocardiogram focused on mitral valve anatomy and ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
2
1
0
Order By: Relevance
“…Based on this, it could be hypothesized that chronic stretch stress on papillary muscles leads to inflammation, fibroblast proliferation, and subsequent fibrosis deposition, contributing to the development of a proarrhythmic substrate. This mechanism may also explain our finding of increased mechanical dispersion in AMVP patients compared to NAMVP patients, which is consistent with the results reported by Vairo et al 25 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Based on this, it could be hypothesized that chronic stretch stress on papillary muscles leads to inflammation, fibroblast proliferation, and subsequent fibrosis deposition, contributing to the development of a proarrhythmic substrate. This mechanism may also explain our finding of increased mechanical dispersion in AMVP patients compared to NAMVP patients, which is consistent with the results reported by Vairo et al 25 …”
Section: Discussionsupporting
confidence: 94%
“…Based on this, it could be hypothesized that chronic stretch stress on papillary muscles leads to inflammation, fibroblast proliferation, and subsequent fibrosis deposition, contributing to the development of a proarrhythmic substrate. This mechanism may also explain our finding of increased mechanical dispersion in AMVP patients compared to NAMVP patients, which is consistent with the results reported by Vairo et al25 A recent study by Scheirlynck et al20 provided evidence of the relationship between myocardial stretch and VA in AMVP patients.They demonstrated that MVP patients with arrhythmias have higher levels of soluble suppression of tumorigenicity 2, a marker released from stretched myocardium, compared to MVP patients without arrhythmias 20. TWI in inferior and lateral leads may be an electrical manifestation of myocardial distress secondary to stretch stress, rather than the expression of a structural abnormality.…”
supporting
confidence: 93%
“…Vairo et al [56] conducted a study, in which they specified some of echocardiographic parameters, which could predict malignant events in arrhythmic MVP patients. They have focused on high-risk features, calculated through spackle tracking analysis, which include: anteroposterior (AP) diameter/AM leaflet (AML) length ratio, the mitral valve annulus indexed area, the inferolateral basal S3 velocity, the AML length, and the basal/mid-ventricular segments mechanical dispersion (DM).…”
Section: Bimvpmentioning
confidence: 99%